PROSEDUR PENGUJIAN SUBSTANTIF ATAS AKUN PIUTANG USAHA PT. MXH PADA KANTOR AKUNTAN PUBLIK JEPTHA, NASIB, DAN JUNIHOL - Rizki Rahmadianti (2022)
Substantive test is one of the audit procedures used to test the fairness of the balances of the accounts presented in the financial statements. Accounts receivable is one of the accounts that must be thoroughly checked. The number of sales transactions, sometimes makes accounts receivable account one of the liquid assets that is often rigged. Recording accounts receivable is quite risky because sometimes there is a mismatch between company records and customers. Therefore, substantive test of receivables needs to be done to determine whether there are monetary errors presented in the company's financial statements. PT. MXH is a company engaged in Information and Communication Technology (ICT), which in its business is included as a company with a fairly stable financial condition experiencing profits. Substantive test procedures performed by the Public Accounting Firm Jeptha, Nasib, and Junihol, namely, measuring the level of materiality, matching balances, checking and testing the age of accounts receivable, confirming balances to third parties, analytical calculations, and vouching. From the results of the tests carried out, it can be concluded that the accounts receivable account belonging to PT. MXH 2021 has been presented fairly without exception.